Determinants of Taxpayer Compliance Through Taxpayer Satisfaction - Rahmi, Iftitah; Defitri, Siska Yulia; Maison, Witra (Institut Bisnis dan Informatika Kesatuan, 2024)
Taxpayer compliance is a taxpayer's action in fulfilling his tax obligations in accordance with the provisions of the applicable laws and regulations in a country. E-Filling is a service for filling out and submitting taxpayer tax returns which is carried out electronically through a real time online system that provides application services or the Directorate General of Taxes website. This study aims to determine the effect of the application of e-Filling and the quality of tax services on taxpayer compliance with taxpayer satisfaction as an intervening variable. The data of this study was obtained from questionnaires (primary). The sampling technique uses the total sampling method. The number of samples in this study was 155 respondents. The technique in data analysis used is Partial Least Square (PLS) with SmartPLS 3.0 software. The results of this study show that the application of e-Filling and the quality of tax services have a positive effect on taxpayer compliance and taxpayer satisfaction, while taxpayer satisfaction does not interfere with the effect of e-Filling implementation and the quality of tax services on taxpayer compliance.